2012
DOI: 10.1159/000337880
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Focal Choroidal Excavation Detected by Spectral-Domain Optical Coherence Tomography

Abstract: Purpose: To report the clinical findings of 2 patients with focal choroidal excavation in the macula detected by spectral-domain optical coherence tomography (SD-OCT). Methods: Three eyes of 2 patients with a focal macular choroidal excavation detected by SD-OCT were studied. The eyes were examined by fundus autofluorescence (FAF), fluorescein angiography, fundus-related microperimetry, and multifocal electroretinography (mfERG). Results: In spite of a complaint of metamorphopsia, the visual acuity was normal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Although Humphrey Visual Field Analysis 10-2 did not show any sensitivity decline, lack of microperimetry, or multifocal electroretinogram, testing fails to detect reduced sensitivity in a very small area or reduced electrophysiologic function. 15 However, we believe that the present case series is the largest study that included detailed clinical examinations to date.…”
Section: Discussionmentioning
confidence: 88%
“…Although Humphrey Visual Field Analysis 10-2 did not show any sensitivity decline, lack of microperimetry, or multifocal electroretinogram, testing fails to detect reduced sensitivity in a very small area or reduced electrophysiologic function. 15 However, we believe that the present case series is the largest study that included detailed clinical examinations to date.…”
Section: Discussionmentioning
confidence: 88%
“…Most were myopic with mean myopia of À 3.5D, which is similar to two previous reports. 3,4 Focal choroidal excavation has been reported to be associated with CSC, ERM, and subretinal neovascularization previously [3][4][5] and more recently CNV 6 and PCV. 7 In our current study, we also found an association with all the above conditions as well as dry AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Margolis et al 4 and Katome et al 6 reported that FCE is common in eyes with a thicker choroid. Ellabban et al 25 reported that the choroidal thickness in CSC eyes with FCE was significantly thicker than that in normal eyes but thinner than that in CSC eyes without FCE.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies using spectral-domain OCT have elucidated the clinical and morphological characteristics of FCE. [2][3][4][5][6][7][8][9][10][11][12] Initially, FCE was considered a stable choroidal abnormality and an incidental finding in patients with metamorphopsia or blurred vision. 10 Recently, it has been suggested that FCE may form the basis of choroidal neovascular diseases.…”
mentioning
confidence: 99%